Design Of A Nonvolatile 8T1R SRAM Cell For Instant-On Operation - J. Mounica; G.V. Ganesh (Institute of Advanced Engineering and Science, 2016)
Now-a-days, Energy consumption is the major key factor in Memories. By switching the circuit in off mode and with an lower voltages, leads to decrease in an power dissipation of the circuit. Compared to DRAM SRAM’S are mostly used because of their data retaining capability. The major advantage of using SRAM’s rather than DRAM’S is that, they are providing fast power-on/off speeds. Hence SRAM’s are more preferred over DRAM’s for better instant-on operation. Generally SRAM’s are classified in to two types namely volatile and non-volatile SRAM’s. A non-volatile SRAM enables chip to achieve performance factors and also provides an restore operation which will be enabled by an restore signal to restore the data and also power-up operation is performed. This paper describes about novel NVSRAM circuit which produces better “instant-on operation” compared to previous techniques used in SRAM’s. In addition to normal 6T SRAM core, we are using RRAM circuitry (Resistive RAM) to provide better instant-on operation. By comparing the performance factors with 8T2R and 9T2R, 8T1R design performs the best in the Nano meter scale. Thus this paper provides better performances in power, energy, propagation delay and area factors as compared with other designs.